Pengaruh Model Discovery Learning dengan Multirepresentasi terhadap Hasil Belajar Fisika Siswa pada Materi Gerak Lurus - Risma Rawanti; I Komang Werdhiana; Marungkil Pasaribu (Faculty of Teacher Training and Education, Musamus University, 2020)
The research objective was to determine whether or not there is an effect of discovery learning model with multiple representations on physics learning outcomes of SMA Negeri 4 Palu students on straight motion material. To find out the students' initial ability in the experimental class and the control class in the straight motion material, a preliminary test was held. After that, the experimental class was treated using a discovery learning model with multiple representations and the control class using a discovery learning model. After learning is complete, the two classes are again given the final test to test the results. Based on the results of the two classes, the final test showed that the experimental class average was 17.93 with a standard deviation of 2.68 and the control class was 16.70 with a standard deviation of 2.53. From the results of the analysis of the final test data, the ttable value is 1.67 and the tcount is 2.05 at the real level α = 0.05 and dk = 68.This shows that the tcount value is outside the receiving area of ​​Ho, thus Ho is rejected and H1 is accepted. . These results indicate that there are differences in learning outcomes between the class that is applied the discovery learning model with the multi-representation model and the class that is applied the discovery learning model. Thus it can be concluded that there is an effect of discovery learning model with multiple representations on physics learning outcomes of SMA Negeri 4 Palu on Straight Motion Material.